Progressive exercise compared with best practice advice, with or without corticosteroid injection, for the treatment of rotator cuff disorders: statistical analysis plan for the Getting it Right: Addressing Shoulder Pain (GRASP) 2 × 2 factorial multicentre randomised controlled trial. - Marian, IR; Hopewell, S; Keene, DJ; Cureton, L; Lamb, SE; Dutton, SJ (BioMed Central, 2020)
Background The Getting it Right: Addressing Shoulder Pain (GRASP) trial assesses the clinical and cost-effectiveness of individually tailored, progressive exercise compared with best practice advice, with or without corticosteroid injection, in adults with a rotator cuff disorder. This article describes the statistical analysis plan for the GRASP randomised controlled trial. Methods/design GRASP is a multicentre randomised controlled trial using a 2 × 2 factorial design. Adults aged ≥ 18 years with a new episode of shoulder pain related to a rotator cuff disorder, not currently receiving physiotherapy or being considered for surgery, are randomised (centralised computer-generated 1:1:1:1 allocation ratio) to one of four interventions: (1) progressive exercise (up to 6 physiotherapy sessions), (2) best practice advice (one physiotherapy session), (3) subacromial corticosteroid injection then progressive exercise and (4) subacromial corticosteroid injection then best practice advice. The primary outcome is the mean difference in Shoulder Pain and Disability Index (SPADI) total score over 12 months. Secondary outcomes are as follows: pain and function SPADI subdomains, health-related quality of life (EuroQol EQ-5D-5L), sleep disturbance, return to activity, global impression of change, health resource use, out-of-pocket expenses and work disability. Here, we describe in detail the following: sample size calculation, descriptive statistics of the primary and secondary outcomes, statistical models used for the analysis of the main outcomes, handling of missing data, planned sensitivity and subgroup analyses. This pre-specified statistical analysis plan was written and submitted without prior knowledge of the trial results. Discussion Publication of the statistical analysis plan for the GRASP trial aims to reduce the risk of outcome reporting bias and increase transparency of the data analysis. Any deviations or changes to the current SAP will be described and justified in the final study report and any results publications. Trial registration International Standard Randomised Controlled Trial Number ISRCTN16539266. Registered on 14 June 2016. EudraCT number 2016-002991-28. Registered on 12 June 2016.